1990
DOI: 10.1039/cs9901900147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and chemistry of acyl silanes

Abstract: Ad B. 13C NMR Spectroscopy.-In comparison with the corresponding ketones, the 13C signals of the carbonyl groups in acyl silanes are dramatically shifted downfield (Table 2).30-31" Carbonyl groups in acyl silanes have chemical shifts differing by between ca. 25 and 100 ppm from those of the analogous ketones; '* the effect is approximately additive (Table 2, entry 16).13C studies also expose some interesting resonance features of acyl silanes. The carbonyl group of an alkyl phenyl ketone (e.g. Ph-CO-But) displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(59 citation statements)
references
References 103 publications
0
55
0
4
Order By: Relevance
“…[10] An alternative, but less used, approach is the one previously described, which includes the addition of a silicon nucleophile to a carbonyl compound. [11][12][13][14] Hiyama et al introduced a fluoride-catalyzed SiÀ Si bond cleavage followed by the addition of released silicon nucleophiles to aldehydes.…”
mentioning
confidence: 99%
“…[10] An alternative, but less used, approach is the one previously described, which includes the addition of a silicon nucleophile to a carbonyl compound. [11][12][13][14] Hiyama et al introduced a fluoride-catalyzed SiÀ Si bond cleavage followed by the addition of released silicon nucleophiles to aldehydes.…”
mentioning
confidence: 99%
“…The dithiane route applicable for the synthesis of a wider range of acylsilanes was studied by Brook et al [24] and Corey et al [25] at the same time in 1967 (Equation (2)). The defect of the method is the use of a toxic mercury compound for the hydrolysis of the silylated dithianes.…”
Section: Introductionmentioning
confidence: 99%
“…During the course of our studies of the reactions of an isolable dialkylsilylene with various functional groups [26][27][28][29][30], we have found that the silylene inserts exclusively into the C-Cl bond of (2) A variety of acylsilanes have been synthesized up to date using different methods, the reactions of protected aldehydes, esters, and other carboxylic acid derivatives, etc. with various silicon reagents [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their discovery by Brook in 1957, 1-3 acylsilanes have been the one of the most powerful and efficient compounds that have the silicon directly attached to the carbonyl group, exhibiting particular physical and chemical properties, [4][5][6][7][8] so that they can be easily transformed into many different derivatives in one pot, such as acid, 9-12 ketone, [13][14][15] alcohol, 16,17 aldehyde, 11,18,19 cyanogen, 20 amide 12,20,21 and ester. 20,22 In addition to these radical reactions, a great deal of effort has been devoted to the development of various other kinds of acylsilane reactions, for instance, stereocontrolled nucleophilic additions, 23 stereocontrolled aldol reactions, 24 cyclization, 25 coupling reaction, 26 α-halogenations, 3 and enantioselective reduction.…”
Section: Introductionmentioning
confidence: 99%